Mitochondrial Abnormalities in Induced Pluripotent Stem Cells-Derived Motor Neurons from Patients with Riboflavin Transporter Deficiency - Fiorella Colasuonno; Enrico Bertini; Marco Tartaglia; Claudia Compagnucci; Sandra Moreno (MDPI AG, 2020)
Riboflavin transporter deficiency (RTD) is a childhood-onset neurodegenerative disorder characterized by sensorineural deafness and motor neuron degeneration. Since riboflavin plays key functions in biological oxidation-reduction reactions, energy metabolism pathways involving flavoproteins are affected in RTD. We recently generated induced pluripotent stem cell (iPSC) lines from affected individuals as an in vitro model of the disease and documented mitochondrial impairment in these cells, dramatically impacting cell redox status. This work extends our study to motor neurons (MNs), i.e., the cell type most affected in patients with RTD. Altered intracellular distribution of mitochondria was detected by confocal microscopic analysis (following immunofluorescence for superoxide dismutase 2 (SOD2), as a dual mitochondrial and antioxidant marker), and βIII-Tubulin, as a neuronal marker. We demonstrate significantly lower SOD2 levels in RTD MNs, as compared to their healthy counterparts. Mitochondrial ultrastructural abnormalities were also assessed by focused ion beam/scanning electron microscopy. Moreover, we investigated the effects of combination treatment using riboflavin and N-acetylcysteine, which is a widely employed antioxidant. Overall, our findings further support the potential of patient-specific RTD models and provide evidence of mitochondrial alterations in RTD-related iPSC-derived MNs-emphasizing oxidative stress involvement in this rare disease. We also provide new clues for possible therapeutic strategies aimed at correcting mitochondrial defects, based on the use of antioxidants.